Impacts of security improvements on service quality in maritime transport : an empirical study of Vietnam - Thai, Vinh Van (2012)
In recent years, maritime security has become a major concern on the international maritime agenda. If security measures and initiatives are not carefully designed and effectively implemented, they can negatively impact the whole maritime transport chain. Security improvements resulting from maritime security requirements may also bring about some benefits to service quality and business performance for the organisation. However, there are limited studies conducted on these aspects. In this paper, we aim to address these gaps by devising a framework of projected impacts of security on service quality in maritime transport and conducting an empirical study to verify the projections. The study was conducted in Vietnam with a group of shipping, port and freight forwarding companies, using the triangulation of both mail survey and in-depth interview techniques. It was evident from this study that all projected relationships between security improvements and service quality are supported by both survey respondents and interviewees. Statistical analysis reveals that, among 13 projected relationships, respondents indicate clear consensus on seven projections, in which security improvements can enhance service quality in terms of increased reliability of service, social responsibility awareness, increased efficiency in operations and management, as well as enhanced image in the market. For the remaining projections, agreement was not clearly shown. This was also reflected in interviews, in which respondents emphasised that the most notable benefits brought about by security improvements are in terms of increased reliability of service performance, increased awareness and better image, thus positively affecting customers' perception of the organisation's service quality. However, these positive impacts are only realised should service providers in maritime transport employ effective security management strategies.